You are Here: Home >< Maths

p3 differentiation watch

Announcements
1. by taking logarithms, prove that if x=3^(1-t)

dx/dt= -(ln3)3^(1-t)

the way ive done it is:

lnx=(1-t)ln3 .dx
1/x=-ln3
1=)-ln3)x
1=(-ln3)3^(1-t)

where did the 1 come from?? thanks for your help
2. I'm not too sure what you've done. But:

lnx = (1-t).ln3 (by taking logs of both sides)

(1/x)(dx/dt) = -ln3 (implicit differentiation)

dx/dt = -xln3

But x = 3(1-t)

=> dx/dt = (-ln3).3(1-t)
3. thanks mokel, i forgot to include the dx/dt bit, otherwise it would have worked.
cheers

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: May 19, 2005
Today on TSR

Four simple steps to get an A*

Here's all you have to do

University open days

• University of East Anglia
All Departments Open 13:00-17:00. Find out more about our diverse range of subject areas and career progression in the Arts & Humanities, Social Sciences, Medicine & Health Sciences, and the Sciences. Postgraduate
Wed, 30 Jan '19
• Aston University
Wed, 30 Jan '19
• Solent University
Sat, 2 Feb '19
Poll
Useful resources

Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

How to use LaTex

Writing equations the easy way

Study habits of A* students

Top tips from students who have already aced their exams

Chat with other maths applicants